2020
DOI: 10.3389/fnins.2020.00719
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 and Protein Aggregation in Parkinson’s Disease: Insights From Animal Models

Abstract: Mutations in leucine-rich repeat kinase 2 (LRRK2) instigate an autosomal dominant form of Parkinson's disease (PD). Despite the neuropathological heterogeneity observed in LRRK2-PD, accumulating evidence suggests that alpha-synuclein and tau pathology are observed in a vast majority of cases. Intriguingly, the presence of protein aggregates spans both LRRK2-PD and idiopathic disease, supportive of a common pathologic mechanism. Thus, it is important to consider how LRRK2 mutations give rise to such pathology, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 93 publications
0
12
1
Order By: Relevance
“…Up to the present study, pomalidomide has not been evaluated in mammalian models of PD. In a recent study, we reported its efficacy in a Drosophila LRRK2 WD40 genetic PD model [16,65]. In that study, we showed that LRRK2 WD40 flies develop motor impairment and gradual loss of dopaminergic neurons with age [16], and pomalidomide administration through the diet prevented both age-dependent motor impairment and neuronal loss [16].…”
Section: Discussionmentioning
confidence: 98%
“…Up to the present study, pomalidomide has not been evaluated in mammalian models of PD. In a recent study, we reported its efficacy in a Drosophila LRRK2 WD40 genetic PD model [16,65]. In that study, we showed that LRRK2 WD40 flies develop motor impairment and gradual loss of dopaminergic neurons with age [16], and pomalidomide administration through the diet prevented both age-dependent motor impairment and neuronal loss [16].…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, IMiDs decreased the α-Syn-induced inflammatory response also in non-motor regions of the brain such as the hippocampus, an area involved in cognitive deficits of PD, supporting a role of neuroinflammation in these non-motor symptoms ( Valera et al, 2015 ; Williams-Gray et al, 2016 ). A recent study demonstrated the pomalidomide efficacy in a drosophila LRRK2 WD40 mutant PD model, with LRRK2 being a common genetic cause of PD ( Casu et al, 2020 ; Dues and Moore, 2020 ). These flies develop motor impairment and gradually lose dopaminergic neurons with age ( Casu et al, 2020 ).…”
Section: Imids and Neurodegenerative Disorders: Preclinical And Clinical Evidencementioning
confidence: 99%
“…Considered to be second most persisting/recurring ND worldwide with multifaceted etiologies, Parkinson’s disease affects approximately 1–2% of the population [ 18 , 19 ]. An intra-neuronal buildup of protein aggregates and Lewy bodies (consisting of misfolded α-synuclein) and gradual decline of dopaminergic neurons in the substantia nigra pars compacta [ 20 , 21 ] are the two major neuropathological processes involved in Parkinson’s disease. Patients with Parkinson’s suffer from a variety of non-motor symptoms, uncontrollable tremors, and diminished motor function that exacerbate in the later stages of the disease [ 22 , 23 ].…”
Section: Brief Overview Of Neurodegenerative Diseases (Nds)mentioning
confidence: 99%
“…Huntington’s disease is an inherited ND characterized pathologically by diminished functions of gamma-aminobutyric acid and excessive dopaminergic activity in the basal ganglia. Clinically, it is characterized by psychiatric disturbance, abnormal movements, and cognitive deficits [ 21 ], being associated with the expansion of the trinucleotide repeat in the Huntington (Htt) gene present at the short arm of chromosome 4. Htt (mutant) proteolysis has been observed to contribute to its pathology, but its role is not yet well defined [ 39 ].…”
Section: Brief Overview Of Neurodegenerative Diseases (Nds)mentioning
confidence: 99%